# UNIVERSITY OF MALTA FACULTY OF SCIENCE DEPARTMENT OF MATHEMATICS MAT1801 Mathematics for Engineers I Problem Sheet 3

(1) Find 2 linearly independent solutions for the following diﬀerential equations (a) y − 3y + 2y = 0; Ans. y1 (x) = ex , y2 (x) = e2x (b) 10y + 6y + y = 0;
x x Ans. y1 (x) = e− 10 x cos 10 , y2 (x) = e− 10 x sin 10
3 3

(c) 25y + 20y + 4y = 0. Ans. y1 (x) = e− 5 x , y2 (x) = xe− 5 x (2) Find a particular solution of the following nonhomogeneous equations by the method of undetermined coeﬃcients.
1 (a) y + 2y + y = cos2 x. Use cos2 x = 2 + 1 cos 2x; 2 1 3 Ans. yp (x) = 2 − 50 cos 2x + 4 50
2 2

sin 2x

(b) y + y − 6y = (x2 − 4)ex + e2x . 1 Ans. yp (x) = 1 xe2x + ( 19 − 3 x − 4 x2 )ex 5 32 8 (3) Solve the diﬀerential equation dy d2 y − 2 + y = 3 sinh x. 2 dx dx Ans. y(x) = ex (Ax + B) + 3 (2x2 ex − e−x ) 8 (4) If z = sin x and if y is a function of x, show that d2 y d2 y dy = 2 cos2 x − sin x. dx2 dz dz

1

Transform the diﬀerential equation d2 y dy tan x − y cos2 x = 2esin x cos2 x + 3 sin x cos2 xe2 sin x + 2 dx dx into an equation connecting y and z, where z = sin x. By ﬁnding two linearly independent solutions of the corresponding homogeneous equation and a particular solution of the nonhomogeneous equation, ﬁnd the general solution of the resulting second order diﬀerential equation with constant coeﬃcients. Give the ﬁnal answer in terms of y and x. Find also the solution which 1 5 satisﬁes the conditions y = − 3 and y = − 3 when x = 0. d2 y − y = 2ez + 3ze2z , dz 2 4 y(x) = Aesin x + Be− sin x + (sin x − 3 )e2 sin x + sin xesin x , 4 y(x) = e− sin x + (sin x − 3 )e2 sin x + sin xesin x Ans. dy d2 y d2 y dy dy = and x2 2 = 2 − . Hence, (5) If x = ez , show that x dx dz dx dz dz or otherwise, solve the equation d2 y dy x2 2 − 3x + 5y = 3x + ln x. dx dx
1 Ans. y(x) = t2 (A sin(ln x) + B cos(ln x)) + 50 (75x + 10 ln x + 8)

(6) A particle starts from rest at the origin O at time t = 0 and moves along the axis Ox so that its distance x from O at time t satisﬁes the diﬀerential equation d2 x dx + 2k + (k 2 + n2 )x = ae−kt cos pt, 2 dt dt where a, k, p and n are positive constants. Find x in terms of t and deduce the solution of the diﬀerential equation with the same initial conditions when p = n. a −kt a cos(pt) − a cos(nt) −kt e , x(t) = te sin(nt) Ans. x(t) = n2 − p2 2n

2